Design of A Website-Based Repository System With The Boyer-Moore Algorithm for Efficient Document Management - Rizky Maulana; Rinna Rachmatika (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The development of information technology demands a system capable of managing documents effectively and efficiently. PT. Prasty Mitra Solusindo still faces obstacles in document archiving, which often causes difficulties in finding the required documents. This research aims to design and develop a web-based repository system by implementing the Boyer-Moore algorithm to improve the efficiency of document retrieval. The development method used is Rapid Application Development (RAD), consisting of planning, design, construction, and implementation stages. The Boyer-Moore algorithm is applied as a text-search method to accelerate the process of document retrieval based on keywords, The testing results show that the developed repository system can significantly speed up the document retrieval process compared to conventional search methods. In addition, the system also supports document management features such as uploading, categorization, and access control, Therefore, this web-based repository system can assist the company in managing documents more quickly, systematically, and easily accessible.